DEVELOPMENT OF LECTORA INSPIRE LEARNING MEDIA IN BEAUTY SUBJECTS IN CLASS X STUDENTS OF TATA KECANTIKAN AT SMK IMELDA MEDAN - Pinte Ni Ateni; Siti Wahidah; Vita Pujawanti Dhana (Jurnal Tata Rias dan Kecantikan, 2022)
This research was conducted at SMK Imelda Medan located on Jalan Bilal No. 52 Pulo Brayan Darat 1, East Medan District. The type of research used is Research and Development (R&D). The object of this study is lectore inspire learning media and the subjects in this study are material experts, media experts, teachers and class X students of beauty management of SMK Imelda Medan. The results of the study proved that the interactive learning media Lectora Inspire facial massage material is suitable for use as a learning medium in schools. The feasibility of the media developed was assessed from the aspect of metering which obtained a score of 90.87% categorized as very feasible. Meanwhile, the assessment results on the media aspect obtained a score of 97.27% categorized as very feasible. The results of the questionnaire of small group trial students on the learning media developed were 90.30% categorized as very good. The results of the response of the students of the medium group trial to the learning media developed were 86.25% well categorized and the results of the response of the students of the large group trial to the learning media developed by 84.35% were well categorized So that it can be concluded that the learning media Lectora Inspire facial sequencing (massage) material developed by researchers is feasible and can be well received by students as a learning medium in the classroom.